Production of polysaccharide bioflocculants and gene co-expression network analysis in a biomass-degrading bacterium, Pseudomonas sp. GO2. (April 2022) - Guo, Haipeng; Fu, Xuezhi; Chen, Yifan; Feng, Jiayin; Qi, Zhenyu; Yan, Mengchen; Zheng, Bingsong; Qin, Wensheng; Shao, Qingsong
Abstract: Several bacteria exhibit reveal excellent production ability of bioflocculants through directly utilizing untreated biomass. However, mechanisms of bioflocculant synthesis in these bacteria remain to be fully clarified. In this study, a biomass-degrading bacterium Pseudomonas sp. GO2 produced a polysaccharide bioflocculant with the maximal flocculating efficiency of 91.5% when corn stover was used as the sole carbon source. To investigate the molecular mechanism of bioflocculant production, the transcriptome of GO2 strain was measured. Using pairwise comparisons and WGCNA analysis, a total of 1032 differentially expressed genes (DEGs) were successfully divided into four co-expression modules. Among them, one specific module (turquoise) was closely associated with CMCase and xylanase activities, and two modules (brown and yellow) were significantly related to the flocculating efficiency. Finally, DEGs related to seven CAZymes and eight secretory proteins were identified as key candidate genes, and seven potential gene clusters associated with these genes may play important roles in biomass degradation and bioflocculant synthesis in GO2 strain. The results not only enrich genomic resource but also provides a solid theory foundation for the rational synthesis of high efficient and low cost bioflocculants.